PENGARUH BEBAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN - heri saptomo yulius; Margareth Sabarofek; Fachira Fachira (Cakrawala Management Business Journal, 2020)
This study aims to determine whether the workload, compensation and partial and simultaneous work environment of employee work discipline at PT. Bank Rakyat Indonesia (Persero) Tbk Manokwari Branch Office. This type of research is associative quantitative research. The sample used in this study was 53 respondents with a sampling technique using Nonprobability Sampling. Data collection uses observation, interviews, and questionnaires. The results of this study prove that work is significant for employee work discipline, significant compensation for employee work discipline, and work environment significantly affects employee work discipline. Simultaneously the workload, compensation and work environment are significant for employee work discipline.